Ketahanan Keluarga di Tengah Pandemi Covid-19 - Yanti, Devi; julia aridhona (Fakultas Ekonomi Universitas Islam Majapahit, 2022)
Family resilience is the family's ability to manage resources and problems to achieve prosperity as well as to survive and adapt to various conditions that are constantly changing, and have a variety of positive attitudes towards life's challenges. Family social and psychological resilience is one of the dimensions in family resilience, which is an important dimension in realizing a harmonious, safe and psychologically prosperous family. Kuta Alam District is an area of ??Banda Aceh City with the highest number of cases of the spread of Covid 19, for this reason, researchers want to examine the condition of family resilience in Kuta Alam District. The family resilience being studied is seen from the socio-psychological dimension. The approach of this research is descriptive quantitative by taking a sample of the location of several villages in the district of Kuta Alam, with a sample of 110 people. The method of data collection is in the form of a questionnaire. Overall, the condition of the family's psychological social resilience is in the moderate category. From the results of this study, it is suggested that families can cope with emotions positively by doing activities that they enjoy, increasing positive self-concept, establishing communication with family members and various covid-19 prevention programs from the central and regional governments aimed at families and must be implemented immediately. and right on target in order to restore the socio-psychological conditions of the community. Keywords: family resilience, social psychology, covid-19 pandemic